Emotional Customer Experience (ECX) in “Phygital” Smart Store Environment (London Journal of Research In Management & Business, 2023)
Smart retail technologies have a significant impact on the emotions of customers in a phygital environment, such as a smart store. This study assessed how and if these technologies act as emotional trigger/source with impacts on the emotional customer experience (ECX).  These technologies appeared to enhance convenience, saving time, and improving the overall shopping experience. The novelty and fascination of these technologies, as well as the resulting concept of smart stores (“just-walk-out” concept), often led to surprise and excitement among customers. These mostly positive emotions were often triggered by the self-service aspects and functionalities of the smart retail technologies Ambivalent or negative emotions arose from the omission of human interaction or the threat to customers’ privacy.  In summary, the study found that smart retail technologies can create a positively designed customer experience through a novel, seamless process, time saving and reducing friction during the entire customer journey. These lead to emotions such as surprise, happiness, or excitement, which trigger an overall contentment in customers. The disruption of privacy, ignorance of existing technologies can lead to negative ECXs, expressed through worry or discontentment. Implications over hospitality, tourism, and other service contexts are provided along with recommendations for future research.
Keywords: the internal combustion engine (ICE); engine; system; Indicator diagram; ultra-high compression; inversely proportional; qualitative.; Phygital environments; Smart stores; Emotional customer experience; ECX.